Classification of type 1 diabetes and type 2 diabetes based on administrative registry data: a nationwide study from Norway - Paz Lopez-Doriga Ruiz; Lars C. Stene; Karianne Fjeld Løvaas; Grethe Åstrøm Ueland; Tone Vonheim Madsen; Kåre I Birkeland; Hanne Løvdal Gulseth; Robert Wiik; Kjersti Nøkleby; Inger Johanne Bakken (Scandinavian Journal of Public Health, 2026)
Background: Type 1 diabetes (T1D) and type 2 diabetes (T2D) differ in health care needs. Precise prevalence estimates by type are important for health care planning. Data and methods: This validation study used Norwegian health registry data to develop a T1D/T2D classification method, using the Norwegian Diabetes Register for Adults (NDR-A) as reference standard. Our study population consisted of all individuals 18 years and older residing in Norway in 2022 ( N = 4,315,563). We used Cohen’s kappa to assess agreement between the classification method and the NDR-A. Results: The established classification method had three key steps: (a) T1D, based on insulin use and specialist health care T1D diagnoses, (b) T2D, based on specialist and primary health care T2D, and (c) T1D, based on primary health care T1D and insulin use, and no T2D. The overall agreement with NDR-A diagnosis was 95.2% for T1D and 97.6% for T2D. For T1D, agreement was 97% or higher in age-groups 18–39 and 40–59, 87.6% for those aged 60–79 and 69.4% for individuals older than 80. For T2D, the agreement was 97% or higher for age-groups 40 and above, and 92.1% for those aged 18–39. Applying the classification method to total population data showed that, in 2022, among 4,315,563 individuals aged 18 and older living in Norway, 31,264 had T1D (0.72%) and 239,120 had T2D (5.5%). Conclusions: Our registry-based classification agreed well with the NDR-A, implying that administrative health registry data are suitable in epidemiological and health services studies of T1D and T2D.